AUTHORS AND BOOKS CITED IN MATTHAEUS PRAETORIUS’S “CHRONICLES OF THE PRUSSIAN CHURCH” - LUKŠAITĖ, INGĖ (Knygotyra, 2010)
The article presents an analysis of the list of publications cited in the footnotes and text of Chronicum ecclesiasticum Prussorum (Chronicle of the Prussian Church), the seventh book of Deliciae Prussicae, oder preussische Schaubühne (Prussian Curiosities or the Prussian Theatre), the manuscript by Matthaeus Praetorius (ca. 1635–1704). The manuscript of M. Pretorius’s Chronicle was fund to contain 231 footnotes at the bottom of the pages and more than 100 references in the text itself. M. Praetorius cites 100 authors and approximately 130 publications. From the chronological standpoint, the cited authors range from the 2nd century to 1698, the year of the completion of the Chronicle manuscript. The article discusses the following main groups of the topics and genres of the cited publications: chronicles and histories of the Teutonic Order and the Duchy of Prussia; chronicles and authorial histories published by historians of Poland and the Grand Duchy of Lithuania from the 15th to the first half of the 17th century; histories of the European Church; histories of regional Churches; texts of late-antique and medieval Christian theologians; key texts of the Lutheran theological doctrine and some Catholic theological texts of the 16th century; writings by regional theological polemists of the 16th–17th centuries. From the religious perspective, M. Praetorius refers to writings of the Church Fathers, early Christian and medieval theologians, authors representing Lutheran, Catholic (among them Jesuits), Calvinist, Aryan and Czech Brethren Churches of the 16th–17th centuries; he extensively cites texts pertaining to intra- and extra-Lutheran polemical disputes; in the end of the Chronicle he gives an account of the authors who seeked reconciliation within the Lutheran Church or between among Western European Churches. The majority of the cited authors and publications come from Central and Central Eastern Europe. The most often cited publication is the Bible. The texts concerning the Lutheran theological doctrine are cited most extensively. The selection of the sources was determined by the goals of the Chronicle: to write a history of regional Churches (those of Royal Prussia, Pomerania and of the Duchy of Prussia, which had been changing its political status throughout the 17 th century), and thereby it is oriented towards the early Christian and medieval Church historians and theologists, important for the theological disputes that took place in the region in the 16th–17th centuries.In the Chronicle, M. Praetorius cites a representative selection of contemporary and medieval authors writing on the topic of particular importance to him: the possibilities for the Prussians to encounter Christianity and the beginnings of their Christianization. His selection of historians of Poland and the Grand Duchy of Lithuania of the 15th–17th centuries is also comprehensive. The foundations of his erudition were laid in the German Evangelical universities and strengthened through independent studies of regional historians’ writings. The list of authors and publications cited by M. Praetorius in the Chronicle shows him as a very well-read, professionally qualified historian. From the broad repertoire of Central and Central Eastern European publications of the 16th–17th centuries, he opts for those that were relevant for his purposes; however, he essentially omits the works that fostered the new history-writing paradigms of the late 16th and 17th century. Fom the contemporary authors, he tends to select the ones who sought reconciliation within the Lutheran Church or among different Western European Churches and thereby laid the foundation for the Pietist and Irenic movements.
Keywords: ...